Aplikasi Simulasi Enkripsi Menggunakan Metode Caesar Cipher Berbasis Website - Fiqri Dian Priyatna Sinaga; Khoiratul Azmi; Afri Yunda Nasution; Rivaldi Prima Nanda; Ibnu Rusydi (Cosmic Jurnal Teknik, 2025)
Cryptography is a fundamental field in data security; however, it is often considered difficult for beginner students due to its abstract and mathematical nature. Previous studies indicate that learning Caesar Cipher is commonly conducted through theoretical approaches or desktop-based applications with limited interactivity and accessibility. Therefore, this study aims to develop a web-based Caesar Cipher encryption simulation application as an interactive learning medium. The system was developed using the prototype method, while functional testing was conducted using the black box testing approach. The effectiveness of the application was evaluated through primary data collected through questionnaires distributed to students. The results show that before using the application, 82.4% of students were at low to moderate levels of understanding, whereas after using the application, 100% of students reached a high level of understanding. These findings indicate that the web-based Caesar Cipher simulation application is effective in improving students’ understanding of fundamental cryptographic concepts prior to studying more advanced data security algorithms